Anterior Cruciate Ligament Femoral Tunnel Placement: An Analysis of the Intended Versus Achieved Position for 221 International High-Volume ACL Surgeons. Issue 5 (April 2020) - Robinson, James; Inderhaug, Eivind; Harlem, Thomas; Spalding, Tim; Brown, Charles H.
Background: Femoral tunnels that are not anatomically placed within the native anterior cruciate ligament (ACL) footprint during ACL reconstruction are associated with residual instability, graft rupture, and poor clinical outcomes. Although surgeons may intend to place their femoral tunnels within the native ACL attachment, this is not always achieved. This study assesses the variation between intended and achieved femoral tunnel positions in a large cohort of experienced ACL surgeons. Hypothesis: The accuracy with which experienced ACL surgeons achieve their intended femoral tunnel position is dependent on viewing portal, localization strategy, and drilling technique. Study Design: Controlled laboratory study. Methods: A total of 221 surgeons indicated their intended femoral tunnel location on a true lateral radiograph of a cadaveric knee specimen and a scaled photograph. Each surgeon then arthroscopically demonstrated the femoral tunnel on the specimen. The position was captured using fluoroscopy. The Euclidean distance (the straight-line distance between 2 points) between the intended and achieved tunnel positions, referenced to a grid applied to the lateral femoral condyle, was compared. Data were analyzed according to surgeons' viewing portal (anteromedial [AM] or anterolateral [AL]), tunnel localization strategy (offset aimer, estimation from landmarks, ACL ruler, or C-arm fluoroscopy), and stated drilling technique (transtibial, AM portal, or outside-in). Results: Surgeons who viewed the lateral intercondylar notch wall through the AM portal were closer (mean distance, 9.5) to their intended position than those who viewed through the AL portal (mean distance, 15.1; P < .0001). By localization strategy, the mean distance between achieved and intended tunnel positions was greater for surgeons who used an offset aimer (14.5) and estimated the femoral tunnel position (12.9) than for those using a malleable ACL ruler (8.1; P < .0001) and fluoroscopy (4.3; P < .0001). Surgeons' preferred drilling technique (AM portal, transtibial, or outside-in) had no effect on distance between intended and achieved positions. However, the mean achieved position was higher in the intercondylar notch for those using transtibial drilling ( P < .042). Conclusion: Surgeons using the AM portal to view the femoral attachment site were closer to their intended tunnel position than those who viewed it with the arthroscope in the AL portal. Surgeons who used fluoroscopy to localize femoral tunnel position were the closest to their intended position. Those who used estimation or an offset aimer had the farthest distance between achieved and intended tunnel positions. Clinical Relevance: Although accurate tunnel placement can be achieved using any method, given the disparity between intended and achieved tunnel positions, it may be advisable, even for high-volume surgeons, to verify the placement of their tunnels using either fluoroscopy or a malleable ACL ruler to ensure that they achieve their intended position. Fluoroscopy may be particularly useful for cases where the native femoral stump is no longer visible and for revisions. Viewing through the AM portal is recommended to aid accuracy of tunnel placement.